Circulating thioredoxin suppresses lipopolysaccharide-induced neutrophil chemotaxis - Nakamura, Hajime (The National Academy of Sciences, 2001)
Thioredoxin (Trx), a redox enzyme with a conserved active site (Cys-32–Gly–Pro–Cys-35), is induced and secreted into circulation in response to inflammation. Studies here demonstrate that elevating Trx levels in circulation either by i.v. injection of recombinant Trx or stimulating Trx release in Trx-transgenic mice dramatically blocks lipopolysaccharide (LPS)-stimulated neutrophil migration in the murine air pouch chemotaxis model. Furthermore, we show that leukocyte recruitment induced by the murine chemokines KC/GROα, RANTES (regulated upon activation, normal T cell expressed and secreted), and monocyte chemoattractant protein-1 (MCP-1) is suppressed also in Trx-transgenic mice. Addressing the mechanism responsible for this suppression, we show that circulating Trx blocks (i) the LPS-stimulated in vitro activation of neutrophil p38 mitogen-activated protein kinase, (ii) the normal down-regulation of CD62L on neutrophils migrating into the LPS-stimulated air pouch, and (iii) the in vitro adhesion of LPS-activated neutrophils on endothelial cells. However, as we also show, Trx does not alter the expression of endothelial cell adhesion molecules (intercellular adhesion molecule-1, vascular cell adhesion molecule-1, CD62P, and CD62E) within 3 h. Collectively, these findings indicate that elevated levels of circulating Trx interfere with chemotaxis by acting directly on neutrophils. We discuss these findings in the context of recent studies reporting beneficial effects of acutely elevated Trx in ischemic injury and negative effects associated with chronically elevated Trx in HIV disease.